Comprehensive Comparison of Clinically Relevant Grain Proteins in Modern and Traditional Bread Wheat Cultivars - Lakhneko, Olha; Danchenko, Maksym; Morgun, Bogdan; Kováč, Andrej; Majerová, Petra; Škultéty, Ľudovit (International journal of molecular sciences, 2020)
Bread wheat (Triticum aestivum L.) is one of the most valuable cereal crops for human consumption. Its grain storage proteins define bread quality, though they may cause food intolerances or allergies in susceptible individuals. Herein, we discovered a diversity of grain proteins in three Ukrainian wheat cultivars: Sotnytsia, Panna (both modern selection), and Ukrainka (landrace). Firstly, proteins were isolated with a detergent-containing buffer that allowed extraction of various groups of storage proteins (glutenins, gliadins, globulins, and albumins); secondly, the proteome was profiled by the two-dimensional gel electrophoresis. Using multi-enzymatic digestion, we identified 49 differentially accumulated proteins. Parallel ultrahigh-performance liquid chromatography separation followed by direct mass spectrometry quantification complemented the results. Principal component analysis confirmed that differences among genotypes were a major source of variation. Non-gluten fraction better discriminated bread wheat cultivars. Various accumulation of clinically relevant plant proteins highlighted one of the modern genotypes as a promising donor for the breeding of hypoallergenic cereals.
Keywords: 2D gelová elektroforéza; Triticum; obilninové proteiny; gluteny; Edible Grain; jedlá semena; proteom; Grain Proteins; Gliadin; globuliny; Proteome; chléb; lidé; Albumins; Globulins; albuminy; Electrophoresis, Gel, Two-Dimensional; Glutens; pšenice; gliadin; Bread; Humans